(untitled) (Journal of Computational Mathematics, 1984)
A comparison by Wang and Xu between S. Samle's cost estimation for Newton's method and that of the author's for Kuhn's algorithm, both aiming at the zero finding of complex polynomials, showed improvements the advantage of the latter in finding zeros and approximate zeros. In this paper, important on the above work are made. Furthermore, a probabilistic estimation of the monotonicity of Kuhn's algorithm is obtained.